Comparison of Removing Double-J Stent With and Without Cystoscopy in Kidney Transplant Patients: A Randomized Clinical Trial - Nadjafi-Semnani, Mohammad; Simforoosh, Nasser; Basiri, Abbas; Tabibi, Ali; Nadjafi-Semnani, Ali (Urology Journal, 2020)
Purpose: The ureteric stent can be attached to the Foley catheter in kidney transplantation to exclude cystoscopy for its removal. It is rarely practiced in renal transplantation. There has been no randomized trial to evaluate the outcome of this procedure on major urologic complications. Materials and Methods: One hundred sixty-three kidney transplant patients were randomized into an intervention group in which the stent was attached to the Foley catheter and removed together and a control group in which stent was removed by cystoscopy. In both groups, stents were removed around the 8th post-operative day. Results: From March 2016 to June 2017, out of 234 kidney transplants performed in our center, one hundred Sixty-three (69.6%) patients met the study inclusion criteria. 91patients (55.8%) were allocated to the intervention group. Mean days before JJ removal for intervention and control groups (“per-protocol” group) were 8.08 ± 1.52 and 8.57 ± 1.58, respectively (P = .09). There was no difference between groups regarding major urologic complications (P = .679). Visual analog scale pain scores were significantly higher in the control group (p = .001). The procedure reduced 63-120 USD from the cost of operation in the intervention group. Conclusion: In selected kidney transplant patients, attaching stent to the Foley catheter and removing both of them early may be a safe maneuver regarding major urological complications, reduces pain, and eliminates the cost of cystoscopy. Keywords: cystoscopy; double-J-stent; kidney transplantation; stent; ureteric stenting